PENGARUH PELAKSANAAN RAWAT GABUNG DENGAN PRODUKSI ASI PADA IBU POST SECTIO CAESAREA - Ni Nyoman Tri Susanthi (Jurnal Keperawatan Priority, 2021)
Exclusive breastfeeding was the providing breast milk (ASI) without any food or drinks other than breast milk, except for drugs, vitamins, or mineral drops. Most mothers often experience problems in implementing exclusive breastfeeding. These were some of the factors causing the low exclusive breastfeeding for newborns. One of the main reasons low breast milk provision in the community is unsmooth breast milk production. Rooming-in concept care is to increase breast milk production. The purpose was to determine the correlation between the implementation of rooming-in care the breast milk production in post-cesarean mothers. This study was a correlational analytic study with a cross-sectional approach method. The sample in this study was nonprobability sampling with consecutive sampling with a total sample of 53 respondents. Data analysis is using Spearman Rank analysis. The results of the Spearman Rank analysis showed that the p-value was 0,000, the means that the hypothesis of this study was accepted, which means that there was a correlation between the implementation combined care with the production of breast milk for post-cesarean section mothers with a correlation coefficient of 0.830. The results of this study have implications in the form of improving the quality of patient safety (patient safety) and patient satisfaction with maternal and child services.